1987
DOI: 10.1093/ptj/67.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Soleus Muscle Electromyographic Activity and Ankle Dorsiflexion Range of Motion During Four Stretching Procedures

Abstract: Volitional muscle contractions are used frequently in some combination with muscle stretching to promote muscle relaxation and to increase range of motion. In this study, muscle lengthening procedures were evaluated in the ankle plantar flexors. Four soleus muscle stretching procedures--static stretch (SS), hold relax (HR) (isometric plantar flexor contraction before stretch), agonist contract (AC) (dorsiflexor contraction assisting stretch), and hold relax-agonist contraction (HR-AC)--were performed in the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
1
19

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 26 publications
8
44
1
19
Order By: Relevance
“…A number of studies report greater ROM improvements after PNF compared with SS within a single session (Etnyre and Lee 1988;Ferber et al 2002;O'Hora et al 2011). On the other hand, SS has also been shown to provide ROM increases similar to those of PNF within a single session (Condon and Hutton 1987;Maddigan et al 2012). There is also conflict in the DS literature, with some studies reporting that an acute bout of DS provides either similar (Beedle and Mann 2007;Perrier et al 2011) or greater (Duncan and Woodfield 2006;Amiri-Khorasani et al 2011) increases in flexibility than does SS, whereas many other studies have reported that DS was not as effective as SS within a single preactivity routine (Samuel et al 2008;Bacurau et al 2009;Sekir et al 2010;Barroso et al 2012;Paradisis et al 2014).…”
Section: Acute Effects Of Ss Ds and Pnf On Joint Rommentioning
confidence: 99%
“…A number of studies report greater ROM improvements after PNF compared with SS within a single session (Etnyre and Lee 1988;Ferber et al 2002;O'Hora et al 2011). On the other hand, SS has also been shown to provide ROM increases similar to those of PNF within a single session (Condon and Hutton 1987;Maddigan et al 2012). There is also conflict in the DS literature, with some studies reporting that an acute bout of DS provides either similar (Beedle and Mann 2007;Perrier et al 2011) or greater (Duncan and Woodfield 2006;Amiri-Khorasani et al 2011) increases in flexibility than does SS, whereas many other studies have reported that DS was not as effective as SS within a single preactivity routine (Samuel et al 2008;Bacurau et al 2009;Sekir et al 2010;Barroso et al 2012;Paradisis et al 2014).…”
Section: Acute Effects Of Ss Ds and Pnf On Joint Rommentioning
confidence: 99%
“…Various stretching techniques are used to improve flexibility (Chang et al, 2002), among which the PNF technique is known to be highly effective in increasing ROM; however, there is still some controversy regard this technique. During stretching, resistance is affected by both the viscoelastic properties of the tissues and the contractile components (Condon et al, 1987). The PNF technique is considered to increase flexibility by decreasing active resistance (Osternig et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the activities of the quadriceps femoris muscles and simultaneous contraction of the hamstring muscles (as agonistic muscles if they are to be stretched) induced relaxation of the muscles surrounding the hip and knee joints. Condon et al 32) and Ostering et al 33) also reported on the usefulness of relaxation involving contraction of agonistic muscles.…”
Section: Effect Of Standing-up In the Elderlymentioning
confidence: 99%